Protein kinase B/AKT phosphorylates hypoxia-inducible factor-3α1 in response to insulin, promoting cell growth and migration - Tran Vinh Hong Nguyen; Ulrich Bergmann; Thomas Kietzmann; Daniela Mennerich (Frontiers in Cell and Developmental Biology, 2023)
Hypoxia-inducible factors (HIFs) are best known for their roles in the adaptation to low oxygen environments. Besides hypoxia, HIF-1/2 α-subunits are also regulated by various non-hypoxic stimuli including insulin which can act via the PI3K/protein kinase B (PKB) signaling pathway. However, with respect to insulin little is known about HIF-3α. We aimed to investigate this relationship and found that insulin stimulates HIF-3α expression under both normal and low oxygen conditions. Blocking PKB activity reversed the effects of insulin, indicating that HIF-3α is a direct target of PKB. We identified serine 524, located in the oxygen-dependent degradation domain of HIF-3α, as a phosphorylation site of PKB. Mutating serine 524 impaired binding of PKB to HIF-3α and its ubiquitination, suggesting that PKB regulates HIF-3α stability through phosphorylation, thereby affecting important cellular processes such as cell viability and cell adhesion. Importantly, we discovered that this phosphorylation site also influenced insulin-dependent cell migration. These findings shed light on a novel mechanism by which insulin affects PKB-dependent HIF-3α expression and activity, with potential implications in metabolic diseases and cancer.